Oyster Versatile IKKα/βs Are Involved in Toll-Like Receptor and RIG-I-Like Receptor Signaling for Innate Immune Response - Huang, Baoyu; Zhang, Linlin; Xu, Fei; Tang, Xueying; Li, Li; Wang, Wei; Liu, Mingkun; Zhang, Guofan (Frontiers in Immunology, 2019)
IκB kinases (IKKs) play critical roles in innate immunity through signal-induced activation of the key transcription factors nuclear factor-κB (NF-κB) and interferon regulatory factors (IRFs). However, studies of invertebrate IKK functions remain scarce. In this study, we performed phylogenetic analysis of IKKs and IKK-related kinases encoded in the Pacific oyster genome. We then cloned and characterized the oyster IKKα/β-2 gene. We found that oyster IKKα/β-2, a homolog of human IKKα/IKKβ, responded to challenge with lipopolysaccharide (LPS), peptidoglycan (PGN), and polyinosinic-polycytidylic acid [poly(I:C)]. As a versatile immune molecule, IKKα/β-2 activated the promoters of NF-κB, TNFα, and IFNβ, as well as IFN-stimulated response element (ISRE)-containing promoters, initiating an antibacterial or antiviral immune state in mammalian cells. Importantly, together with the cloned oyster IKKα/β-1, we investigated the signal transduction pathways mediated by these two IKKα/β proteins. Our results showed that IKKα/β-1 and IKKα/β-2 could interact with the oyster TNF receptor-associated factor 6 (TRAF6) and that IKKα/β-2 could also bind to the oyster myeloid differentiation factor 88 (MyD88) protein directly, suggesting that oyster IKKα/βs participate in both RIG-I-like receptor (RLR) and Toll-like receptor (TLR) signaling for the reception of upstream immune signals. The fact that IKKα/β-1 and IKKα/β-2 formed homodimers by interacting with themselves and heterodimers by interacting with each other, along with the fact that both oyster IKKα/β proteins interacted with NEMO protein, indicates that oyster IKKα/βs and the scaffold protein NEMO form an IKK complex, which may be a key step in phosphorylating IκB proteins and activating NF-κB. Moreover, we found that oyster IKKα/βs could interact with IRF8, and this may be related to the IKK-mediated activation of ISRE promotors and their involvement in the oyster “interferon (IFN)-like” antiviral pathway. Moreover, the expression of oyster IKKα/β-1 and IKKα/β-2 may induce the phosphorylation of IκB proteins to activate NF-κB. These results reveal the immune function of oyster IKKα/β-2 and establish the existence of mollusk TLR and RLR signaling mediated by IKKα/β proteins for the first time. Our findings should be helpful in deciphering the immune mechanisms of invertebrates and understanding the development of the vertebrate innate immunity network.